Have Investment and Technology Been Effective in Reducing Unemployment? (An Analysis in Indonesia Using Generalized Method of Moment) - Sri Indriyani Siregar (Nusantara Science and Technology Proceedings, 2022)
To achieve the SDGs (Sustainable Development Goals), especially the 8th goal, the government needs to be concerned about reducing unemployment. Two of the government's efforts are increasing investment and ICT (information and communication technology), where this study aims to evaluate the effectiveness of these efforts and other economic indicators on unemployment rates. This study uses the provincial panel of Indonesia data from 2012 to 2020, which is analyzed through dynamic panel data regression with the Generalized Method of Moment (GMM) Arellano-Bond approach. This analytical method is used because the variables are dynamic and able to estimate the short-run as well as the long-run effect. The results show that Domestic Direct Investment (DDI), economic growth, and regional minimum wages significantly reduce unemployment rates. Furthermore, the elasticity results show that for every 1 percent increase in domestic investment in a province, it will reduce the unemployment rate in the short run by 0.144 percent and in the long run by 0.205 percent. Meanwhile, ICT development is proven to increase unemployment, where every 1 percent increase will increase unemployment in the short run by 0.501 percent and in the long run by 0.713 percent. This study can be used as an evaluation material for the government and the stakeholders. Especially, to formulate strategies so that technological development does not become a time bomb for employment problems. In addition, increasing investment, dominantly from domestic, in the sectors that absorb many laborers is needed to accelerate the economy wheel performance.